Insulation system diagnosis in power transformers using DGA analysis and Megger DC tests - Juris Zapata, Juan Sebastian; Marulanda Guerra, Agustín Rafael; Tello Maita, Josimar Dadi; Duran Tovar, Ivan Camilo (My University, 2024)
Dissolved gas chromatography (DGA) analysis and Megger DC insulation tests are performed to diagnose the condition of a power transformer. In this context, the objective of this study is to assess whether there is a relationship between both types of tests. To this effect, a database with DGA and Megger DC test protocols is analyzed, using the theory of variable correlation as well as current DGA techniques. The results allow stating that there is indeed a relationship between both tests under specific conditions. Therefore, the DC isolation status of a transformer can be estimated via DGA tests.

Los analisis por cromatografıa de gases disueltos (DGA) y las pruebas de aislamiento Megger DC son realizados para diagnosticar el estado de un transformador de potencia. En este contexto, el objetivo de este estudio es evaluar si existe una relacion entre ambos tipos de pruebas. Para ello, se analiza una base de datos con protocolos de pruebas DGA y Megger DC, utilizando la teorıa de correlacion de variables y las tecnicas actuales de DGA. Los resultados permiten afirmar que sı existe una relacion entre ambas pruebas bajo condiciones especıficas. Por lo tanto, se puede estimar el estado de aislamiento DC de un transformador a partir de pruebas DGA.
Diagnóstico de sistemas de aislamiento en transformadoresde potencia utilizando análisis DGA y pruebas Megger DC
Digital
Keywords: Técnicas de impulsos (Electrónica); Pulse techniques (Electronics); Cromatografía; Chromatographic analysis; Dieléctricos; Dielectrics; Insulation; Correlation; Chromatography; Maintenance; Aislamiento; Correlación; Cromatografía; Mantenimiento